A Statistical Study on Impact of Facebook Usage of Engineering Students at VIT - C, Keerthika; Raghavan, Manisha; V.M, Chandrasekaran (International Journal of Engineering and Technology, 2018)
This study aims to find the influence that Facebook plays as a social networking medium on engineering students at an undergraduate level in VIT, Vellore. Facebook, a prominent online social media and networking site was founded and launched in 2004 by Mark Zuckerberg. Facebook has been under the scanner to study the influence it has on human emotional health, social life and mental health. Facebook has grown to become one of the most prevalent Social Networking Sites (SNS) in this era. A lot of previous studies have tried to study the role Facebook has played not only on students or adolescents but also on adults and all. During this study, we have tried to see the role that Facebook plays in an engineering undergraduate studentâ€™s life especially the extent to which it affects the studentsâ€™ academic performance. Various studies have shown that Facebook plays a major role in influencing emotions, moods and attitudes of students. We aim to understand the role that Facebook plays buy administering a survey amongst students in the University and analyse the extent to which students are affected by using it. The survey constituted of 16 questions and was administered to about 250 respondents belonging to the undergraduate engineering student pool. The method of sampling done was simple random sampling and data analysis was done using SPSS.Â